The evolution of shareholder voting for executive compensation schemes - Morgan, Angela; Poulsen, Annette; Wolf, Jack (Journal of Corporate Finance, 2006)
We examine shareholder voting on management-sponsored compensation proposals from 1992 through 2003 to determine how voting has evolved as a result of changes in the corporate governance environment. We investigate three questions: have regulatory changes and changes in investor sentiment affected voting; do the same factors appear to influence voting over time and has the impact of the various factors changed over time; and do additional factors such as the level of compensation and alternate definitions of dilution influence voting support? We find evidence of changing trends in voting, that shareholders have become more sensitive to potentially harmful plan provisions, and that additional factors do affect voting.